Massive Secondary Postpartum Hemorrhage with Uterine Artery Pseudoaneurysm after Cesarean Section - Ahmet Ozgur Yeniel; Ahmet Mete Ergenoglu; Ali Akdemir; Elmin Eminov; Fuat Akercan; Nedim Karadadaş (Case Reports in Obstetrics and Gynecology)
Uterine artery pseudoaneurysm is a rare but serious complication of cesarean section. If inadequately treated, it can lead to life-threatening postpartum hemorrhage. Herein, we report the case of a 28-year-old woman who developed secondary postpartum hemorrhage resulting from uterine artery pseudoaneurysm and cesarean scar dehiscence after cesarean section. Angiographic embolization is a safe and effective procedure for treating postpartum hemorrhage resulting from pseudoaneurysm in hemodynamically stable patients. However, uterine artery ligation may be the surgical procedure of choice for hemodynamically unstable patients when fertility preservation is desired.